Right Coronary Artery Originating From Mid Left Anterior Descending Artery: A Rare Variant of Anomalous Right Coronary Artery Detected on CT Coronary Angiography. - Husin, Mohd Hafizuddin; Mohamad Jamali, Ahmad Aizuddin; A Hamid, Mohd Azaad; Saad, Khairulanuar (Journal Of Cardiovascular, Neurovascular & Stroke, 2022)
Background: A single coronary artery (SCA) is a rare anomaly encountered using conventional coronary angiography. A right coronary artery (RCA) originating from a left anterior descending artery (LAD) is a rare subtype of SCA. Only a few cases are described in published literature. Case presentation: We described this anomaly in a 55-year-old male who presented with angina pectoris. The anomalous RCA was suspected by conventional coronary angiogram and was confirmed by computed tomography (CT) coronary angiography. Using CT, we demonstrated the course of the abnormal vessel and its relation to the main vessel. We also detected the presence of plaque, which caused luminal stenosis of the proximal LAD, which may cause global ischaemia. Conclusion: We concluded that although conventional coronary angiography is an important diagnostic method, new non-invasive methods such as CT coronary angiography can be a better screening tool to detect and characterise coronary anomalies. Electronic Supplementary Materials Supplementary Material 1: Coronary angiogram demonstrates anomalous RCA originating from LAD. Supplementary Material 2: CTA coronary shows anomalous RCA originates from the mid-portion of LAD.